- INDONESIAN CULTURE DIPLOMACY THROUGH MOTOGP IN THE KEK MANDALIKA INTERNATIONAL CIRCUIT: - - Muhammad Aji Bangkit Pratama; Harahap, Ali Musa (UNIDA GONTOR, 2023)
This research discusses Indonesia's cultural diplomacy through the MotoGP event at the KEK Mandalika international circuit. MotoGP is a motor racing championship event at the highest level in the world which is then used as an instrument in Indonesian cultural diplomacy activities towards other countries. Overall this research seeks to explain how Indonesia makes the MotoGP event a medium in Indonesian cultural diplomacy. To explain this issue, this study uses the theory of cultural diplomacy and nation branding as an analytical lens. This study uses a qualitative research method with a qualitative exploratory design that is relevant in describing Indonesia's efforts in carrying out its cultural diplomacy and branding Indonesia in the MotoGP event. This study also uses data collection techniques with literature studies and documentation studies. While the data analysis technique in this study is by reduction, data presentation, and drawing conclusions. The results of this study show that cultural diplomacy carried out by Indonesia in the MotoGP event consists of several efforts, starting with establishing the Mandalika area as one of the 5 DSP (super priority destinations), the Indonesian government also applies aspects of 3 A (accessibility, amenities, attractions ) to KEK Mandalika, the Indonesian government also held a MotoGP pre-event, namely UMKM Goes to Mandalika, these efforts were the steps of the Indonesian government in carrying out cultural diplomacy in the form of exhibitions where tourism objects were the means and recognition were the goal.